PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT ELECTRONIC CITY INDONESIA TBK CABANG SUDIRMAN - Bulloh; Melda Wiguna (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of work discipline and work motivation on the performance of employees at PT Elektronic City Indonesia Tbk Sudirman branch, both partially and simultaneously. The method used is quantitative. The sampling technique consisted of 50 respondents. Data analysis uses validity tests, reliability tests, classical hypothesis tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis tests. The results of this research show that work discipline has a significant effect on employee performance with the regression equation Y = 12,370 + 0.699X1. Hypothesis tests obtained a calculated t-value > table t or (6.462 > 2.011). Thus, H0 is rejected and H1 is accepted, which means that there is a significant influence between work discipline on employee performance at PT Elektronic City Indonesia Tbk Sudirman branch. Work motivation has a significant effect on employee performance with the regression equation Y = 21,546 + 0.478X2. The hypothesis tests obtained a calculated t-value > t-table or (6.566 > 2.011). Thus, H0 is rejected and H2 is accepted, which means that there is a significant influence of work motivation on employee performance at PT Elektronic City Indonesia Tbk Sudirman branch. Work discipline and work motivation have a significant effect on employee performance with the regression equation Y = 9,542 + 0.453X1 + 0.316X2. Hypothesis testing obtained a calculated F value > F table or (37.400 > 3.20). Thus H0 is rejected and H3 is accepted. This means that there is simultaneously a significant influence between work discipline and work motivation on employee performance of PT Elektronic City Indonesia Tbk Sudirman Branch.